(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Throughout the Covid-19 pandemic, the Director-General of the World Health Organization (WHO) has emphasized that “all countries must find the ideal balance between protecting health, minimizing economic and social disruption and respecting human rights.” With health systems overwhelmed, countries need to make difficult decisions to balance the demands of a direct response to Covid-19 while engaging in strategic planning and coordinated action to maintain the delivery of essential health services. Providing many services will become more complex. However, women’s choices and rights to sexual and reproductive health should be respected regardless of Covid-19 status. To guide national health systems in planning the strategic shifts needed to maintain sexual and reproductive health services and respond to the additional demands of the Covid-19 pandemic, WHO has published specific resources on Covid-19 that complement existing resources in this area [1].